2007
DOI: 10.1097/wnr.0b013e3280e129f5
|View full text |Cite
|
Sign up to set email alerts
|

Dreams recall and auditory evoked potentials during propofol anaesthesia

Abstract: It is unclear whether shorter wave latencies of middle-latency-auditory-evoked-potentials may be associated to cognitive function other than nondeclarative memory. We investigated the presence of declarative, nondeclarative and dreaming memory in propofol-anaesthetized patients and any relationship to intraoperatively registered middle-latency-auditory-evoked-potentials. An audiotape containing one of two stories was presented to patients during anaesthesia. Patients were interviewed on dream recall immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…10 In previous studies, dreams reported after anaesthesia are usually pleasant, short, simple, related to everyday life, and unrelated to the operative setting. 10,13,22,23 Our findings partially corroborate previous results as the dream reports were brief, only a quarter of the dream experiences were dynamic, and positive emotional states were slightly more frequent than negative emotional experiences.…”
Section: Discussionsupporting
confidence: 89%
“…10 In previous studies, dreams reported after anaesthesia are usually pleasant, short, simple, related to everyday life, and unrelated to the operative setting. 10,13,22,23 Our findings partially corroborate previous results as the dream reports were brief, only a quarter of the dream experiences were dynamic, and positive emotional states were slightly more frequent than negative emotional experiences.…”
Section: Discussionsupporting
confidence: 89%
“…When the patients opened their eyes at the end of anaesthesia, they were immediately asked whether they recalled any dreams, and if so, were requested to describe the details. Approximately 24 h after surgery, patients were asked a series of open‐ended questions to probe explicit recollection of intra‐operative events : ‘What is the last thing you remember before falling asleep?’, ‘What is the first thing you remember upon awakening?’, ‘Did you dream while you were asleep?’, ‘Did you hear any words or sounds while you were asleep?’ Implicit memory was investigated using a story‐related free association test .…”
Section: Methodsmentioning
confidence: 99%
“…Incomplete abolition of cognitive faculties such as memory and learning during anaesthesia has been studied for many years . Interestingly, in most cases anaesthetic drugs cause obliteration of explicit memory, whereas implicit memory and/or dream recall may sometimes be preserved . Previous studies have tried to identify the relationship between implicit memory or dream recall and depth of anaesthesia using EEG‐derived parameters .…”
mentioning
confidence: 99%
See 2 more Smart Citations